Leucine-rich repeat proteins of Leptospira interrogans that interact to host glycosaminoglycans and integrins - Foltran, Bruno B.; Teixeira, Aline F.; Romero, Eliete C.; Fernandes, Luis G. V.; Nascimento, Ana L. T. O. (Frontiers in Microbiology, 2024)
Pathogenic spirochaetes of the genus Leptospira are the etiological agents of leptospirosis, a zoonotic infection worldwide. The disease is considered an emerging and re-emerging threat due to global warming, followed by heavy rainfall and flooding when outbreaks of leptospirosis occur. Adhesion to host tissues is mediated by surface/extracellular proteins expressed by pathogens during infection. Leucine-rich repeat (LRR) domain-containing proteins seem to be important for the virulence of pathogenic Leptospira and their role has been recently examined. Here, we report the characterization of two LRR-proteins encoded by LIC11051 and LIC11505. They present 7 and 17 LRR motifs, respectively. LIC11051 was found mainly in the P1 subclade, whereas LIC11505 was identified with higher identity in subclade P1, but was also found in subclades P2, S1, and S2. The recombinant proteins were recognized by antibodies in leptospirosis serum samples, suggesting their expression during infection. rLIC11505 contains a broad spectrum of ligands, including GAG and integrin receptors, whereas rLIC11051 showed limited binding activity. The attachment of proteins to ligands was specific, dose-dependent, and saturable. Compared to their role in adhesion, both proteins were shown to be secreted, with the ability to reassociate with the bacteria. Taken together, our data suggested that LIC11051 and LIC11505 participate in leptospiral pathogenesis. To the best of our knowledge, this is the first report showing leptospiral LRR-proteins exhibiting GAG and integrin receptor-binding properties.